Spatial Changes in Soil Organic Matter and Waste Elements in Contaminated Agricultural Fields at Anthropogenically Transformed Areas within the East Calcutta Wetlands Ecosystem - Sudin Pal, Sanjoy Chakraborty and Subhra Kumar Mukhopadhyay, Shuvadip Adhikari*, Anandamay Barik (Journal of the Indian Society of Soil Science, 2021)
Physical and chemical properties of soil were compared between different agricultural fields of multi-metal waste contaminated East Calcutta Wetlands (ECW) sites and uncontaminated control study sites. Soil organic matter (SOM) contents were significantly different between contaminated ECW and control sites. Agricultural fields at ECW sites were characterized by higher contents of SOM, porosity, moisture, particle size (sandy >63 Âµm) and metals; while the control sites had higher bulk density, pH and electrical conductivity (EC). Metal accumulation in soils of ECW showed the trend Fe>Zn>Mn>Cr>Pb>Cu; while at control sites like Fe>(Zn=Mn)>Cr>(Pb=Cu). Post-Hoc analyses (with Tukey HSD) clearly pointed out site-wise significant differences (at p